2009
DOI: 10.1007/s10961-009-9122-6
|View full text |Cite
|
Sign up to set email alerts
|

Review panel consensus and post-decision commercial performance: a study of early stage technologies

Abstract: Grant review, Commercialization success, Prediction, Panel consensus, O32,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Using an alternative metric, Galbraith et al showed that peer reviewers’ opinions were only weakly predictive of the commercial success of early stage technologies in small businesses ( Galbraith et al , 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using an alternative metric, Galbraith et al showed that peer reviewers’ opinions were only weakly predictive of the commercial success of early stage technologies in small businesses ( Galbraith et al , 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…First, the evaluation of the submitted ideas was executed solely by a jury of experts. However, experts may exhibit only a limited ability to evaluate quality (Galbraith, DeNoble & Ehrlich, 2008) and unduly reject submitted ideas (Möslein, Haller & Bullinger, 2010). Future studies should investigate whether expert evaluation or open evaluation by a group of evaluators of such user groups (Möslein, Haller & Bullinger, 2010) is the better assessment method.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…To differentiate between technologies we used the concept of the technology readiness level (TRL), as adopted by Mankins (2009). We acknowledge the critique that the perception of technology readiness is highly dependent on organizational specifics (Heslop et al, 2001) and that it is difficult to precisely determine the commercialization potential of early-stage technologies (Galbraith et al, 2010). Nonetheless, we use the TRL terminology as it allows for cross-case comparisons.…”
Section: Case Study Selection and Data Collectionmentioning
confidence: 99%